2016
DOI: 10.1074/jbc.m116.749655
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated endogenous C-terminal Tagging of Trypanosoma cruzi Genes Reveals the Acidocalcisome Localization of the Inositol 1,4,5-Trisphosphate Receptor

Abstract: Edited by Dennis VoelkerMethods for genetic manipulation of Trypanosoma cruzi, the etiologic agent of Chagas disease, have been highly inefficient, and no endogenous tagging of genes has been reported to date. We report here the use of the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR-associated gene 9) system for endogenously tagging genes in this parasite. The utility of the method was established by tagging genes encoding proteins of known localization such as TcFCaBP (flag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 43 publications
3
73
0
3
Order By: Relevance
“…We recently demonstrated that endogenously tagged TcMCU localizes to the mitochondria of T. cruzi (17). TcMCU-OE protein also localized to the mitochondria, as demonstrated by immunofluorescence microscopy (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that endogenously tagged TcMCU localizes to the mitochondria of T. cruzi (17). TcMCU-OE protein also localized to the mitochondria, as demonstrated by immunofluorescence microscopy (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5C). It has previously been shown that a tagged protein may be retained in the endoplasmic reticulum on its way to the final destination 39 .
Figure 5TbIRK co-localizes with a marker for acidocalcisomes. Co-localization of hemagglutinin (HA)-tagged TbIRK (green) with the acidocalcisomal marker TbVP1 (red) for C-terminally tagged TbIRK in procyclic form parasites (PCF, A ) and N-terminally tagged TbIRK in bloodstream form parasites (BSF, B ).
…”
Section: Resultsmentioning
confidence: 87%
“…PCR conditions will vary depending on PCR product size. Figures 7A and 7D show examples of PCR analysis of TcVP1 gene tagged with 3xHA and 3xc-Myc, respectively (Lander et al ., 2016b). …”
Section: Materials and Reagentsmentioning
confidence: 99%
“…This parasite has been particularly refractory to genetic manipulation (Docampo, 2011). However, the recent use of the CRISPR/Cas9 technology for gene knockout and knockdown (Peng et al , 2014; Lander et al ., 2015) and to perform endogenous gene tagging (Lander et al ., 2016b) has transformed the approaches for functional study of proteins in this organism. Here we describe a protocol to generate CRISPR/Cas9-mediated endogenous gene tagging in T. cruzi , leading to the expression of specific C-terminal tagged proteins in this parasite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation